Optimization of Glycolipid Synthesis in Hydrophilic Deep Eutectic Solvents - Hollenbach, Rebecca; Bindereif, Benjamin; van der Schaaf, Ulrike S.; Ochsenreither, Katrin; Syldatk, Christoph (Frontiers in Bioengineering and Biotechnology, 2020)
Glycolipids are considered as an alternative to petrochemically based surfactants because they are non-toxic, biodegradable and less environmentally harmful while having comparable surface-active properties. They can be produced chemically or enzymatically in organic solvents or in deep eutectic solvents (DES) from renewable resources. DES are non-flammable, non-volatile, biodegradable and (nearly) non toxic. In contrast to organic solvents sugars are easily soluble in hydrophilic DES. However, DES are highly viscous systems and restricted mass transfer is probably a major limiting factor for their application. Limiting factors for glycolipid synthesis in DES are not well understood in general. Therefore, the influence of external mass transfer, fatty acid concentration and distribution on initial reaction velocity in two hydrophilic DES (choline:urea and choline:glucose) was investigated. At agitation speeds of 60 rpm and higher, the viscosity of both DES did not limit external mass transfer. Fatty acid concentration of 0.5 M resulted in highest initial reaction velocity while higher concentrations had negative effects. Fatty acid accessibility was identified as limiting factor for glycolipid synthesis in hydrophilic DES. Mean droplet sizes of fatty acid-DES emulsions can be significantly decreased by ultrasonic pretreatment resulting in significantly increased initial reaction velocity and yield (from 0.15 ± 0.03 µmol glucose monodecanoate/g DES to 0.57 ± 0.03 µmol/g) in the choline: urea DES. The study clearly indicates that fatty acid accessibility is a limiting factor in enzymatic glycolipid synthesis in DES. Furthermore, it was shown that physical pretreatment of fatty acid-DES emulsions is mandatory to improve the availability of fatty acids.